Role of Women Education in the Welfare of Society: The Empowerment of Women through Education (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Although education is considered a necessity, more and more parents are educating their daughter’s still learning household work for a girl is given importance. They cannot negate house hold work to most of women their daughters are helpful in household duties. Educated women also play an important role in major decisions taken in the family about educating marriage of children etc. No longer have women preferred to be with their traditional wifely role. They wish to get knowledge and widen their mental horizon. Girls' education is essential in order to make them independent and as future security for them.